Numerical design of all-dielectric nanophotonic optical tweezers for lossless manipulation of small nanoparticles - Sarria, Jhon James Hernandez (2022)
Conventional optical tweezers are useful in biosciences to manipulate micron-sized objects, DNA molecules, low-dimensional semiconductor structures and metallic nanoparticles using propagating laser beams. However, the effective optical trapping of nanometer-sized biomolecules requires high-power, tightly focused laser beams, which may be unavailable or photodamage temperature-sensitive particles. In order to avoid high power intensities and overcome the diffraction limit of light, plasmonic tweezers are employed to localize, hold and transport bodies of a few nanometers. In this approach, optical fields are confined beyond the diffraction limit in small volumes, with typical sizes of a few tens of nanometers (hotspots) that arise near the surface of a metallic nanostructure when surface plasmons are excited. The strong evanescent near-fields enhance the resulting optical force in the subwavelength regime. Unfortunately, electromagnetic heating due to the Ohmic losses of plasmonic components considerably limits the range of application of plasmonic tweezers, and the stable optical trapping of temperature-sensitive nanometer-scale objects still remains as a challenge. To overcome the Joule heating, sophisticated nanostructures made of high-refractive-index (HRI) materials with electromagnetic field enhancements and confinements have been proposed for optical trapping of nanoscale biological entities. In this PhD thesis, a design is presented of an all-dielectric nanodisk to capture small dielectric achiral and chiral biological molecules without heating its surrounding environment. Using a HRI nanodisk, placed above SiO2 semi-infinite substrate and immersed in water, efficient optical trapping of spherical nanoparticles with radius as small as 12 nm has been achieved. Such stable optical trapping, with the depth of the trapping potential much higher than 10kBT in modulus, has been obtained using the second-order non-radiating anapole mode in an amorphous-Si nanodisk with diameter d = 420 nm and height h = 100 nm, having a rectangular slot at the center. Nanobeads with radius as small as r = 8 nm at the center of the slot experience optical forces of a few pNs, with trapping forces strong enough to move them. These results were reached with a tightly focused laser beam at the infrared and moderate illumination intensities, without producing undesired temperature increases inside nor around the nanostructure. We also demonstrated that all-dielectric nanodisks made of amorphous silicon (a-Si) can exhibit double-well optical potentials. Hence, the simultaneous optical trapping of two nanoparticles in water was numerically investigated to determine the influence that a trapped spherical nanoparticle has on another nearby particle but with a different morphology. This approach may be useful to monitor experimentally the interaction between a pair of biological molecules, such as two proteins or a protein with an antibody, under isolated and controlled conditions. Furthermore, to distinguish enantiomers in a racemic sample a chiral all-dielectric platform with a non-negligible chiroptical activity has been introduced. In this platform, two optical forces, namely, the dielectric and chiral gradient forces, compete to guarantee enantioselectivity in the Rayleigh regime. All the optical properties presented in the thesis were determined utilizing the commercial software COMSOL Multiphysics and Lumerical FDTD. The heat transfer and computational fluid dynamics (CFD) modules were used in a coupled manner in Comsol multiphysics to study numerically the temperature distribution and the thermal-induced fluid motion when the dielectric nanostructures are illuminated with short wavelengths.